Tomato mottle wrinkle virus, a recombinant begomovirus infecting tomato in Argentina - Vaghi Medina, Carlos Gaston; Martin, Darren P.; Lopez Lambertini, Paola Maria (Springer, 2018)
Begomoviruses seriously threaten tomato production in South America. Here, we present the molecular characterization of a novel tomato-infecting begomovirus isolated in Argentina and demonstrate its infectivity. After cloning and sequencing the complete genome of this new virus, pairwise genetic distance and phylogenetic analyses revealed that it is a novel virus that is closely related to other begomoviruses found in Argentina, Brazil and Bolivia. We have proposed naming the virus tomato mottle wrinkle virus (ToMoWrV), based on symptoms produced upon its biolistic inoculation into tomato plants. Recombination analysis revealed that ToMoWrV is a recombinant, with parental sequences likely belonging to the South American begomoviruses soybean blistering mosaic virus (SoBlMV) and tomato yellow vein streak virus (ToYVSV).